Use and abuse of over-the-counter analgesic agents. - Abbott, F V (1998)
Pain and discomfort in everyday life are often treated with over-the-counter (OTC) analgesic medications. These drugs are remarkably safe, but serious side effects can occur. Up to 70% of the population in Western countries uses analgesics regularly, primarily for headaches, other specific pains and febrile illness. It is not known whether the patterns of use are consistent with good pain management practices. OTC analgesics are also widely used to treat dysphoric mood states and sleep disturbances, and high levels of OTC analgesic medication use are associated with psychiatric illness, particularly depressive symptoms, and the use of alcohol, nicotine and caffeine. More than 4 g per day of acetylsalicylic acid (ASA) or acetaminophen over long periods is considered abuse. People using excessive amounts of OTC analgesics may need more effective treatments for chronic pain, depression or dysthymia. The possibility that these drugs have subtle reinforcing properties needs to be investigated. Certainly phenacetin, which was taken off the market in the 1970s, had intoxicating effects. A better understanding of patterns of use is needed to determine the extent of problem use of OTC analgesics, and whether health could be improved by educating people about the appropriate use of these drugs.